Information Services Using Problem Based Learning (PBL) Methods To Increase The Emotional Quotient (EQ) Of Students - Neci Yalisma; Neviyarni Neviyarni; Marjohan Marjohan (International Journal of Applied Counseling and Social Sciences, 2021)
Emotion is a feeling that arises in students, both positive and negative, a phenomenon that often occurs in schools that there are still students who have negative emotions, such as being angry with friends in class, in this study students should be able to regulate emotions so as not to have a negative impact on themselves nor other people. This study aims to increase the emotional quotient of class X and XI students. This research is experimental research, the type of research used is a quasi-experimental design with a nonequivalent control group design. The sampling technique used was purposive sampling. The number of samples of  60 people who are categorized as low on the student's emotional quotient, the class sample is divided into two groups: 1) the experimental group of 30 people and 2) the control group of 30 people. The instrument used was a anemotional quotient questionnaire. The results of the emotional quotient show that there is an increase in the emotional quotient of students between the experimental group before and after the treatment of information services using the problem-based learning method is carried out, there is an increase in the emotional quotient of the control group students before and after being provided with information services without the problem-based learning method, there is a significant difference in the level students' emotional quotient between the experimental group that was provided with information services using the problem-based learning method and the control group that was provided with information services. Thus, information services using problem-based learning methods are effective in increasing students' emotional quotient.